Integrated metabolome and transcriptome analysis reveals key genes and pathways associated with egg yolk percentage in chicken - Wen Li; Yuxing Luo; Shoujia Zhu; Mengyuan Wang; Xuli Zhao; Zhonghua Ning (Poultry Science)
Yolk percentage is a critical index in the egg product industry, reflecting both nutritional value and economic benefits. To elucidate the underlying mechanisms that contribute to variations in egg yolk percentage, we performed integrated transcriptome and metabolome analyses on the liver, ovary, and magnum tissues of Rhode Island Red chickens with high and low yolk percentages. A total of 322 differentially expressed genes (DEGs) and 128 significantly differential metabolites (SDMs) (VIP>1, P < 0.05) were identified in the liver, whereas 419 DEGs and 215 SDMs were detected in the ovary, and 238 DEGs along with 47 SDMs were found in the magnum. In the liver, genes such as HMGCR, DHCR7, MSMO1, and CYP7A1 were linked to cholesterol metabolism, essential for steroid hormone synthesis and yolk formation, while ACACB, ACSL1, ACSL4, LPL, and SGPP2 were involved in fatty acid biosynthesis, a key process for supplying energy and structural components of the yolk. In the ovary, COL6A6, COMP, CHAD, ITGA7, THBS2, and TNC contributed to extracellular matrix–receptor interactions, which are fundamental for follicle development and oocyte maturation. In the magnum, UGT1A1, MAOB, and ALDH3B2 participated in drug metabolism-cytochrome P450 and amino acid metabolism, ensuring a proper environment for egg white formation and potentially influencing nutrient allocation to the yolk. Metabolic pathway enrichment revealed that steroid hormone biosynthesis, glycerophospholipid metabolism, and betaine metabolism were predominant in the liver; pyruvate, taurine, and hypotaurine metabolism in the ovary; and phenylalanine metabolism in the magnum. Moreover, integrated analysis highlighted key metabolites and genes potentially regulating yolk deposition, including 7,8-dihydroneopterin and Pg 38:4 in the liver (related to immune modulation and lipid metabolism, respectively), thalsimine in the ovary, as well as DL-glutamine in the magnum, all of which may be crucial for maintaining metabolic homeostasis and supporting egg formation. Collectively, these findings deepen our understanding of how distinct molecular and metabolic pathways in the liver, ovary, and magnum orchestrate yolk proportion and deposition. Such insights may advance future strategies to improve egg quality and productivity in poultry breeding programs.